ANALISIS LOGAM TIMBAL (Pb) DAN BESI (Fe) DALAM AIR LAUT DI WILAYAH PESISIR PELABUHAN FERRY TAIPA KECAMATAN PALU UTARA (The Analysis of Lead (Pb) and Iron (Fe) Metals in The Sea Water of Coastal Area of Taipa’s Ferry Harbor Subdistrict of North Palu) - Ika, Ika; Tahril, Tahril; Said, Irwan (Universitas Tadulako, 2012)
The analysis of lead (Pb) and iron (Fe) have been done in Taipa’s sea water. The objective is to determine the level of lead and iron metals using spectrophtometry method. The sea water samples were taken in the morning and afternoon at three different places. The distance of 3 samples are approximately 5 m, 10 m, and 15 m from the harbour and about 5 m from the seashore. The result of the analysis level of lead and iron metals from 3 points for lead taken in the morning, point A is 0.919 mg/L, point B is 0.703 mg/L, and point C is 0.810 mg/L. While, taken in the afternoon, the lead level point A is 0.729 mg/L, point B is 0.837 mg/L, and point C is 0.729 mg/L. For the iron level taken in the morning, point A is 0.394 mg/L, point B is 0.546 mg/L, and point C is 0.324 mg/L. Meanwhile, in the afternoon the iron level, point A is 0.449 mg/L, point B is 0.365 mg/L, and point C is 0.504 mg/L. The concentration of lead metal in the sea water is in range 0.703 mg/L – 0.919 mg/L. The concentration is higher than limit ranges value of lead metal 0.025 mg/L. The concentration of iron metal in the sea water of Taipa’s harbor is about 0.324 mg/L – 0.546 mg/L. It’s concentration is higher than limit for value iron metal 0.01 mg/L.